Electrospraying Micronization of Phytochemical Compounds Extract from Eucheuma Cottonii - Dwi Setyorini; Siti Machmudah; Sugeng Winardi; Kusdianto Kusdianto; Wahyudiono Wahyudiono; Hideki Kanda; Motonobu Goto (Jurnal Teknik ITS, 2019)
A side from being a raw material for agar, Eucheuma cottonii algae have many other benefits because they contain various phytochemical compounds. The phytochemical compounds in Eucheuma cottonii have many benefits in the industrial and pharmaceutical fields. A method to get phytochemical compounds is through the extraction process. In the traditional method, the extraction is using organic solvents that dangerous to the environment. Therefore, this study used an environmentally friendly hydrothermal extraction method. Extraction was carried out at 160oC and a pressure of 7 MPa. The extraction results were then micronized using electrospraying. The electrospraying process was carried out with precursor solution concentration of 4 and 6% w/v, the applied voltage of 12, 14 and 16 kV, and the distance between tip and collector of 6.8 and 10 cm. The particles produced was characterized by Scanning Electron Microscope (SEM), Thermal Gravimetry Analysis (TGA), and antioxidant efficiency (AE) analysis. The morphological form of particles were spheres with a diameter below 3 μm. The largest AE value was 0.1818 obtained at operating conditions of 6% precursor solution, 10 cm tip distance, 16 kV applied voltage. The Operating conditions did not affect the TGA results.